Analisis User Experience pada Warehouse Marketplace dengan Metode Heuristic Evaluation - Zahra Syifadeasy Azkya; Irfan Ardiansah; Totok Pujianto (Jurnal Teknik Informatika dan Sistem Informasi, 2020)
A warehouse marketplace is a platform that brings together businesses or people who need a warehouse with a warehouse provider. Because this type of marketplace is relatively new, there are still many shortcomings, especially in the User Experience (UX) section. The features offered by this marketplace are still very limited, so it is difficult to attract potential users. The purpose of this study is to analyze and improve User Experience in the warehouse marketplace. Heuristic evaluation will be used as a UX analyzer method and Google Material Design as a reference of design principles for revising the previous UX. The evaluation results will be useful for two parties. For user to navigate the marketplace easier so that the conversion from visitors to buyers increases. For startups in warehouse category which want to use websites as a marketing and leasing facility to have a good User Experience. Keywords— Heuristic Evaluation; Startup; User Experience; Warehouse; Website.